Production of Bioethanol by Zymomonas Mobilis in High-gravity Extractive Fermentations - Azilah, Ajit; Ahmad Ziad, Sulaiman; Chisti, Yusuf (Elsevier Ltd, 2017)
Continuous removal of ethanol during production by the anaerobic bacterium Zymomonas mobilis mitigated ethanol inhibition. Ethanol inhibited its own production at a concentration of >20 g L−1. Ethanol productivity was enhanced by continuous in situ extraction with water-immiscible organic solvents. Several solvents were evaluated for biocompatibility with Z. mobilis and the ability to extract ethanol from a batch fermentation. In situ batch extractive fermentations were carried out in a 2-L stirred bioreactor (1:1 volume ratio of solvent and fermentation broth) with an optimal glucose concentration of 150 g L−1, 35 °C, and an agitation speed of 150 rpm. Oleyl alcohol, iso-octadecanol and 2-octyl-1-dodecanol were the three solvents that were most compatible with Z. mobilis. With these solvents, the cell viability relative to control (no solvent) was 1.48 ± 0.40, 1.03 ± 0.18 and 1.05 ± 0.07, respectively, after two days of exposure. All solvents tested improved the final biomass concentration, the glucose consumption and ethanol production relative to control, but iso-octadecanol was clearly the most effective solvent. Using iso-octadecanol, the maximum ethanol concentration of 75 ± 3 g L−1 was attained. This was nearly 1.25-fold that of the control fermentation. For this solvent, the ethanol yield on glucose was 0.485 ± 0.005 g g−1 compared to a yield of 0.468 ± 0.005 g g−1 for the control culture.